Skin integrity disorders among patients with chronic venous insufficiency and venous ulcer - Szewczyk, Maria T.; Jawień, Arkadiusz; Cwajda, Justyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Skin is the most important organ which provides integration with environment. Since it is the most external part of human body skin also protects organism from the negative environmental influences. The most important skin function – external protection – depends on skin structure and processes presented in individual parts. Negative impact of external factors or internal disorders may break the skin barrier function and disturb its integrity. One of the most common diseases influencing the skin integrity is chronic venous insufficiency. Associated venous hypertension is a cause of trophic and inflammatory changes of skin and subcutaneous tissue. In severe cases it leads to ulcer development. Study presents external and internal factors disrupting the skin integrity. Pathogenesis and skin complications of chronic venous insufficiency were also presented.